Interspeech 2017 2017
DOI: 10.21437/interspeech.2017-1634
|View full text |Cite
|
Sign up to set email alerts
|

Approximating Phonotactic Input in Children’s Linguistic Environments from Orthographic Transcripts

Abstract: Child-directed spoken data is the ideal source of support for claims about children's linguistic environments. However, phonological transcriptions of child-directed speech are scarce, compared to sources like adult-directed speech or text data. Acquiring reliable descriptions of children's phonological environments from more readily accessible sources would mean considerable savings of time and money. The first step towards this goal is to quantify the reliability of descriptions derived from such secondary s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 14 publications
1
5
0
Order By: Relevance
“…2 siːn.ˌjʉːs.ˌtoerk/) occurring in the corpora. The performance of this method has been tested for Swedish; Strömbergsson et al (2017) found the reliability of the generated phonemic transcripts to be satisfactory, with a point-by-point agreement with manual phonemic transcriptions of 94%.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…2 siːn.ˌjʉːs.ˌtoerk/) occurring in the corpora. The performance of this method has been tested for Swedish; Strömbergsson et al (2017) found the reliability of the generated phonemic transcripts to be satisfactory, with a point-by-point agreement with manual phonemic transcriptions of 94%.…”
Section: Methodsmentioning
confidence: 99%
“…Based on preliminary data presented in Strömbergsson et al (2017), where differences in phonotactic distributions were identified between different types of linguistic data within one and the same language, differences are expected also in what effects simulated error patterns may have. With fewer opportunities where an error pattern is applicable, the smaller the expected effect.…”
Section: Within the Same Language How Does Severity Vary Across A) Th...mentioning
confidence: 99%
See 1 more Smart Citation
“…For words not found in the pronunciation dictionary, phonological transcriptions were generated through grapheme-to-phoneme conversion (Bisani & Ney, 2008). For a more detailed description, see Strömbergsson, Edlund, Götze, and Nilsson Björkenstam (2017). Phonological transcription of observed speech production was conducted by two SLP students (authors MÖCA and CO).…”
Section: Speech Analysismentioning
confidence: 99%
“…So far, studies on the effects of system response delays are rather scarce 3 and controversial. For instance 4 , reported that participants rated a system with 0.60 s faster reaction time as politer, more efficient and more transparent.…”
Section: Introductionmentioning
confidence: 99%